A Possible Relationship between Peri-Implantitis, Titanium Hypersensitivity, and External Tooth Resorption: Metal-Free Alternative to Titanium Implants - Andrea Enrico Borgonovo; Rachele Censi; Virna Vavassori; Mauro Savio; Dino Re (Case Reports in Dentistry)
Titanium dental implant surface does not remain unaltered but may corrode and release ions or particles which trigger soft and hard tissue damage. Titanium may induce clinically relevant hypersensitivity in patients chronically exposed. A 56-year-old female patient presented peri-implantitis around a single titanium implant positioned three years earlier. Despite nonsurgical therapy, a rapid bone loss associated with pain and swelling occurred, and adjacent teeth presented external resorption. Compromised teeth were removed, and three titanium implants were inserted. Six months later, the patient complained about high mucosa sensitivity and implant exposure. At clinical and radiographic examinations, tissue inflammation and vertical bone loss involved the new implants and the process of external resorption affected the teeth. The blood test confirmed titanium hypersensitivity. Titanium implants were removed, and 5 zirconia implants were placed. No sign of bone loss or tooth resorption was recorded at clinical and radiographic control during 18 months of follow-up.